Evaluating the KENARA Program as a Cultural Identity Policy: A Case Study of Gayo Cultural Preservation at SMP IT Cendekia Takengon - Ida Nusraini; Mesiono; Nurussakinah Daulay (JPI: Jurnal Pustaka Indonesia, 2026)
The KENARA Program was initiated as a school-based cultural identity policy to preserve Gayo cultural values among students amid the growing influence of globalization, digital media, and declining intergenerational cultural transmission. This study aims to evaluate the implementation of the KENARA Program at SMP IT Cendekia Takengon, Central Aceh, by examining its context, input, process, and product dimensions. This research employed a qualitative evaluative design guided by the CIPP evaluation model. Data were collected through semi-structured interviews, direct observation, and document analysis involving the principal and teachers who were directly engaged in the program. The data were analyzed through data condensation, data display, conclusion drawing, and verification, while credibility was strengthened through source and technique triangulation. The findings show that, in the context dimension, KENARA has a strong cultural rationale because it responds to the weakening transmission of Gayo language, values, arts, and identity among students. In the input dimension, the program is constrained by limited teacher competence, the absence of standardized modules, inadequate facilities, insufficient funding, and weak structured stakeholder support. In the process dimension, the program has been implemented through cultural habituation, traditional arts, language use, and school-based cultural activities, but its integration into classroom learning remains uneven and its evaluation instruments are not yet standardized. In the product dimension, KENARA has contributed to students’ cultural knowledge, confidence, pride, and participation, although their deeper understanding of Gayo cultural philosophy remains limited. The study implies that cultural identity policies in schools require standardized curriculum guidelines, teacher training, measurable evaluation indicators, and sustained collaboration among schools, families, customary institutions, and local government.